The Structure and Biological Function of CREG - Ghobrial, Gaby; Araujo, Luiz; Jinwala, Felecia; Li, Shaohua; Lee, Leonard Y. (Frontiers in Cell and Developmental Biology, 2018)
The cellular repressor of E1A-stimulated genes (CREG) is a 220 amino acid glycoprotein structurally similar to oxidoreductases. However, CREG does not have enzymatic activities because it cannot bind to the cofactor flavin mononucleotide. Although CREG can be secreted, it is mainly an intracellular protein localized in the endocytic-lysosomal compartment. It undergoes proteolytic maturation mediated by lysosomal cysteine proteases. Biochemical studies have demonstrated that CREG interacts with mannose-6-phosphate/insulin-like growth factor-2 receptor (M6P/IGF2R) and exocyst Sec8. CREG inhibits proliferation and induces differentiation and senescence when overexpressed in cultured cells. In Drosophila, RNAi-mediated knockdown of CREG causes developmental lethality at the pupal stage. In mice, global deletion of the CREG1 gene leads to early embryonic death. These findings establish an essential role for CREG in development. CREG1 haploinsufficient and liver-specific knockout mice are susceptible to high fat diet-induced obesity, hepatic steatosis and insulin resistance. The purpose of this review is to provide an overview of what we know about the biochemistry and biology of CREG and to discuss the important questions that remain to be addressed in the future.